'Many Great Treasures' of 'Great Beauty', or 'Crude and Cramped'? The Appraisal of 'Nineveh's Remains' by Austen Henry Layard, Stratford Canning, and Henry Rawlinson. (28th June 2018) - Hoeks, Robin
One need only point to the destruction caused to the archaeological sites of Iraq and Syria by Islamic State to see an example of the role heritage plays in the construction of identities, and of a past serving a contemporary agenda. Credit for the 'discovery' of the antiquities of Mesopotamia goes to Paul-Émile Botta (1802–1870), and Austen Henry Layard (1817–1894). Most British scholars had long considered the Mesopotamian antiquities to be inferior to Greco-Roman antiquities. Before the 1840's, this group of upper-class critics had been the most important public of the British Museum. During the middle of the nineteenth-century, however, Layard's Assyrian remains became both symbols of, and stakes in, a struggle for wider public access. Their rejection by the critics was contrasted with both historical and aesthetic admiration by the middle- and working classes. Simultaneously, the critics stood on one side of a developing rift between themselves and the archaeologists of a new discipline. In this article I analyse the appraisal of the Mesopotamian sculptures through a critical appraisal of the historiography and an analysis of the Layard Papers, in order to gain a better insight into the reception of the Assyrian antiquities in Victorian Great-Britain.